Undernutrition in Khayelitsha, Crossroads and Browns Farm: A review of nutritional outcomes of children treated at Philani's clinics from 2008 to 2018 - Bill, Claudine (Department of Paediatrics and Child Health, 2022)
Background: Acute and chronic malnutrition continue to impede child health and well-being in South Africa. This study aims to assess the nutritional outcomes of children under five years of age referred for underweight or growth faltering who were treated at Philani clinics in Khayelitsha, Crossroads and Browns Farm. Children were assessed by a medical doctor, and received nutritional supplementation according to the Nutrition Therapeutic Programme guidelines. Methods: We conducted a retrospective cohort study of children under 5 years who attended a Philani clinic between 2008 and 2018. Participants were included if they attended a Philani clinic for a minimum of three months. The primary outcome was rehabilitation of weight-for-age (WAZ) above -2 Standard deviations (SD), according to the World Health Organisation child growth standards. Results: Of 1803 folders screened, 933 met inclusion criteria, from which 592 were randomly selected. There were 326 (55.1%) girls, and the median age of the children at study entry was 7.9 (interquartile range [IQR] 3.5; 14.9) months. The median follow-up period was 9.9 (IQR 6.7; 15.7) months, and the total follow-up period was 621.6 child years. There were high levels of poverty with 401 (67.7%) children living in an informal dwelling and 267 (46.6%) children experiencing a lack of food in their household. Background vulnerability to undernutrition was common, including HIV exposure (n=277, 46.8%), HIV infection (n=45, 7.6%), low birth weight (n=324, 54.7%) and foetal alcohol spectrum disorders (n=36, 6.1%). At study entry, 392 (66.2%) children were assessed as moderately to severely underweight for age. The median WAZ at study entry was -2.6 (IQR -3.4; -1.6) standard deviations (SD) and at exit was -1.7 (IQR -2.5; -0.7) SD; p< 0.001. Of the 392 children underweight at the start, 243 (62.0%; 95% confidence interval (CI) 57.0 – 66.8%) showed improvement. Of these children, 173 (71.2%; 95% CI 65.1 – 76.8%) were rehabilitated to a normal weight, and 70 (28.8%), although not rehabilitated, improved from severely to moderately underweight for age. The median change in WAZ from study entry to exit was 0.2 (IQR -0.3; 0.8) SD for children whose weight was normal at the start; 0.5 (IQR 0.0; 1.2) SD for children who were moderately underweight at the start; and 1.4 (IQR 0.6; 2.6) SD for children who were severely underweight at the start; p=0.0001. Seven children (1.2%) died, all but one without rehabilitation. In total, 164 (27.7%) children were lost to follow-up. Conclusion: Children attending Philani's nutrition clinics come from poor socio-economic conditions, with high rates of poverty and infectious diseases. The intervention delivered by Philani's nutrition clinics was able to improve the nutritional status of over 62% of underweight children. In over 71% of the improved children, the change was to normal weight for age. Children who were severely malnourished at entry to the clinics achieved that largest change in weight-for-age z-scores (WAZ). Philani's structured nutrition intervention provides a model that could be replicated in other vulnerable communities to improve the wellbeing of South Africa's children.